2010
DOI: 10.1111/j.1463-1318.2009.01778.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonic diverticulitis: a prospective analysis of diagnostic accuracy and clinical decision‐making

Abstract: The accuracy of the clinical diagnosis for colonic diverticulitis is low. Ultrasound and computed tomography have superior diagnostic accuracy but these examinations rarely change the initial management proposal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 32 publications
2
73
0
13
Order By: Relevance
“…This recommendation is based on the fact that a lack of imaging results in an increased di- agnostic error rate. Therefore, clinical diagnosis without imaging reaches sensitivities of only between 64 % and 71 % [24,25]. "Qualified abdominal ultrasound" should be used as the primary cross-sectional imaging procedure for the initial and follow-up diagnostic workup of acute diverticulitis.…”
mentioning
confidence: 99%
“…This recommendation is based on the fact that a lack of imaging results in an increased di- agnostic error rate. Therefore, clinical diagnosis without imaging reaches sensitivities of only between 64 % and 71 % [24,25]. "Qualified abdominal ultrasound" should be used as the primary cross-sectional imaging procedure for the initial and follow-up diagnostic workup of acute diverticulitis.…”
mentioning
confidence: 99%
“…As a consequence, however, without CT-scan or operation, no classification of diverticulitis for the vast majority of patients exists, because the hitherto used classifications (Hinchey, Hansen-Stock) were based on either operative or CT-criteria. On the other hand, merely ´clinical diagnosis´ of diverticulitis is insufficient (sensitivity ~65%) and potentially misleading [4,[37][38][39][40]. Also apostrophized as ´left sided appendicitis´, the triad (i) spontaneous pain in the left lower quadrant, exaggerated by movements, (ii) an inflammatory reaction (CRP, WBC, temperature) and (iii) local guarding upon palpation, is unspecific, time-dependent, and variable, and thus may raise the suspicion of diverticulitis but neither satisfies contemporary diagnostic needs nor excludes most differential diagnoses [4,29].…”
Section: Examinermentioning
confidence: 99%
“…It is notable that during the time period of the study, a total of 1,257 patients were admitted with acute diverticulitis; it is unlikely that only 100 of these patients required surgical intervention, thereby raising the possibility of selection bias within the study. There have also been a number of systematic literature reviews regarding laparoscopic lavage, all of which have concluded that the procedure was successful in controlling sepsis in the vast majority of patients, with low morbidity and mortality rates, and could therefore be a valid alternative to a Hartmann's procedure [8,[57][58][59]. However, in general, the published studies included were of low methodological quality.…”
Section: The Role Of Laparoscopic Peritoneal Lavagementioning
confidence: 99%
“…Patients presenting with clinical features of acute diverticulitis are increasingly being investigated by computed tomography (CT), as studies have shown that the accuracy of clinical diagnosis in diverticulitis is low [8,9]. CT has been shown to be more sensitive than water-soluble contrast enema in the assessment of acute diverticulitis [10,11] and can predict the failure of medical treatment and the likelihood of secondary complications [12]; it also has the advantage of allowing the detection of other pathologies.…”
Section: Introductionmentioning
confidence: 99%